Enhancing Students' Speaking Skill Through Active Learning Strategy; A Classroom Action Research - Pajrini, Ani; Mubaidillah; Gustantri, Friska Miranda (Institut Agama Islam Yasni Bungo, 2022)
This research was intended to describe: (a) the process of teaching and learning speaking skill through active learning strategy type everyone is a teacher here, (b) to describe the lecturer’s effort to enhance the students’ speaking skill by using active learning strategy. This was a classroom action research and used Kemmis and Mc Taggart design. It took place at The Institute for Islamic Studies Yasni Bungo. The research participants were the students at the second Semester of Pendidikan Guru Madrasah Ibtidaiyah (PGMI/SD) department, Tarbiyah Faculty. The Institute for Islamic Studies Yasni Bungo academic year 2021/2022. The research was conducted in two cycles. Each cycle consisted of three meetings. In collecting the data, the researcher used observation, field note, interview and tasks. Finding of this research showed that the teaching and learning process through active learning strategy was fun, more interesting and challenging for students and also it made them participate actively in the class activities. There were enhancements on students’ skill after the students taught by using active learning, it could be seen from the enhancement of students’ score from the first cycle to the second cycle. In summary, it can be concluded that the active learning could be used in teaching vocabulary and speaking skill.